The College Students’ Perception of Using @englishfess_ and Engfess Study Club in Learning Grammar Based on Technology Acceptance Model (TAM) in Indonesia - Oktavieni, Asra Fadhilah; Oktoviandry, Rifki (Journal of English Language Teaching, 2024)
This study aimed to find out the college students’ perception in using @englishfess_ and engfess study club in learning grammar. This study used descriptive quantitative research. Questionnaire was used to collect the data. The questionnaire was distributed to the samples who qualified as the sample of this research. By using purposive technique sampling, 89 college students were qualified to be the sample for this study. They were the X users who utilized @englishfess_ and engfess study club to learn grammar and they were the active college students in Indonesia. To measure their perception on using @englishfess_ and engfess study club in learning grammar, researcher used Technology Acceptance Model (TAM). The TAM indicators to measure the college students’ perception were Perceive Usefulness (PU), Perceive Ease of Use (PEOU) and Attitude Toward Use (ATU). The findings of this study show that the college students had very positive perception to the use of @englishfess_ and engfess study club in learning grammar. The easiness of @englishfess_ and engfess study club help them in learning. The students had less pressure when they were using the clubs in learning grammar.